Cogging Torque Reduction Analysis of Radial Field Excitation Coil Flux Switching Motor Using JMAG-Designer Software - Wan Yamin, Wan Safran Aiman; Ahmad, Md Zarafi (Evolution in Electrical and Electronic Engineering, 2022)
Hybrid excitation flux switching machines (HEFSM) is an attractive topic of research and development in recent decades, especially for electric vehicle applications. The HEFSM design proposed a lower permanent magnet consumption, a higher torque density, and a higher efficiency. However, cogging torque is one of the factors which affect the motor in terms of vibration and non-audible noise that become a serious issue in flux switching machines. It is mandatory for every motor to have low cogging torque because having low cogging torque enhances the control based on the positioning of the motor in an electric vehicle drive application. The purpose of this project is to do cogging torque reduction analysis and evaluates the output performances of HESFM with FEC in a radial direction based on the finite element method. The JMAG-Designer version 16 software is used as a two-dimensional (2D) finite element solver. The machine’s performances in terms of cogging torque, back EMF, flux linkage, flux distribution and output torque are also evaluated. Various rotor technique configurations such as notching (NOT) and chamfering (C.H), were examined. Then a new technique has been proposed and compared using a combination of NOT and C.H for reduction of cogging torque. Initially, techniques based on NOT and C.H reduced the cogging torque by 58% and 54% respectively of the original value of 9.6Nm. Then, the proposed technique by combining NOT and C.H has reduced almost 62% of the initial result simultaneously. This result is considered the best-reduced technique for the reduction of cogging torque of HEFSM. The combined technique has successfully reduced the cogging torque which improves motor performance.